IMPROVING STUDENT LEARNING ACTIVITIES THROUGH STUDENT TEAM ACHIEVEMENT DIVISION LEARNING MODEL - Gitta Permata Widyani; Sukirno Sukirno (Jurnal Pendidikan Akuntansi Indonesia, 2019)
A good learning method is a part of the factors that the school manage to improve students’ activities in a class. A cooperative learning model is one of the learning models are often used by teachers in their teaching learning process. This research aims to improve student learning activities through the implementation of student team achievement divisions (STAD) learning model. This research is a Classroom Action Research conducted in two cycles involving 30 students of class XII Social 1 SMA N 1 Wonosari academic year 2018/2019. Data were collected with an observation and a documentation equipped with observation sheets, observation guidelines, and field notes. Analysis of the data used a qualitative and quantitative approach consisting of data processing, data presentation and drawing conclusions. The result shows that the Implementation of STAD learning model can improve Accounting Learning Activities of students Class XII Social 1 SMA N 1 Wonosari supported by an increase in average of learning activities score from 56,02% (in cycle I) to 92,07% (cycle II). Results are discussed and recommendation are provided.Keywords: Accounting Learning Activities, STAD